Presence of Roe Deer Affects the Occurrence of Anaplasma phagocytophilum Ecotypes in Questing Ixodes ricinus in Different Habitat Types of Central Europe - Hamšíková, Zuzana; Silaghi, Cornelia; Takumi, Katsuhisa; Rudolf, Ivo; Gunár, Kristyna; Sprong, Hein; Kazimírová, Mária (International journal of environmental research and public health, 2019)
The way in which European genetic variants of Anaplasma phagocytophilum circulate in their natural foci and which variants cause disease in humans or livestock remains thus far unclear. Red deer and roe deer are suggested to be reservoirs for some European A. phagocytophilum strains, and Ixodes ricinus is their principal vector. Based on groEL gene sequences, five A. phagocytophilum ecotypes have been identified. Ecotype I is associated with the broadest host range, including strains that cause disease in domestic animals and humans. Ecotype II is associated with roe deer and does not include zoonotic strains. In the present study, questing I. ricinus were collected in urban, pasture, and natural habitats in the Czech Republic, Germany, and Slovakia. A fragment of the msp2 gene of A. phagocytophilum was amplified by real-time PCR in DNA isolated from ticks. Positive samples were further analyzed by nested PCRs targeting fragments of the 16S rRNA and groEL genes, followed by sequencing. Samples were stratified according to the presence/absence of roe deer at the sampling sites. Geographic origin, habitat, and tick stage were also considered. The probability that A. phagocytophilum is a particular ecotype was estimated by a generalized linear model. Anaplasma phagocytophilum was identified by genetic typing in 274 I. ricinus ticks. The majority belonged to ecotype I (63.9%), 28.5% were ecotype II, and both ecotypes were identified in 7.7% of ticks. Ecotype II was more frequently identified in ticks originating from a site with presence of roe deer, whereas ecotype I was more frequent in adult ticks than in nymphs. Models taking into account the country-specific, site-specific, and habitat-specific aspects did not improve the goodness of the fit. Thus, roe deer presence in a certain site and the tick developmental stage are suggested to be the two factors consistently influencing the occurrence of a particular A. phagocytophilum ecotype in a positive I. ricinus tick.
Keywords: deer; Ixodes; Europe; RNA, Ribosomal, 16S; lidé; RNA ribozomální 16S; Ecotype; Humans; Evropa; ekotyp; Ecosystem; Animals; ekosystém; Ixodes ricinus; Deer; vysoká zvěř; zvířata; klíště; ecotype; Anaplasma phagocytophilum